2017
DOI: 10.5004/dwt.2017.21321
|View full text |Cite
|
Sign up to set email alerts
|

Highly facile removal of Acid Red 88 from aqueous samples by using synthesized iron oxide magnetic nanoparticles and 1-butyl-3- methylimidazolium tetrachloroferrate magnetic ionic liquid

Abstract: a b s t r ac tIn this study, the application of synthesized Fe 3 O 4 magnetic nanoparticles and 1-butyl-3-methylimidazolium tetrachloroferrate (bmim [FeCl 4 ]), as a magnetic ionic liquid, for removal of Acid Red 88 (AR88) from aqueous solution was investigated. At first, Fe 3 O 4 magnetic nanoparticles (MNPs) were synthesized via a chemical co-precipitation method with drop-wise addition of sodium hydroxide to an ideal mole ratio mixture of Fe 2+ and Fe 3+ solutions (Fe 2+ /Fe 3+ ), about 0.5, as well as und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…As seen in Fig. 3, the dark nano-Fe 3 O 4 cores have been surrounded by a gray shell of SDS micelle and SiO 2 coating, and also little agglomeration can be observed [13]. Moreover, from TEM report, the particles have an approximate spherical shape and an average size of 30-40 nm.…”
Section: X-ray Powder Diffraction (Xrd)mentioning
confidence: 77%
See 3 more Smart Citations
“…As seen in Fig. 3, the dark nano-Fe 3 O 4 cores have been surrounded by a gray shell of SDS micelle and SiO 2 coating, and also little agglomeration can be observed [13]. Moreover, from TEM report, the particles have an approximate spherical shape and an average size of 30-40 nm.…”
Section: X-ray Powder Diffraction (Xrd)mentioning
confidence: 77%
“…Therefore, monolayer adsorption of dye on the homogeneous surface of SDS micelle-coated Fe 3 O 4 /SiO 2 MNP has been considered. Since the constant 1/n is 0.174, proper physical adsorption of dye on the nanoadsorbent is concluded [13]. On the other hands, the results showed that the maximum capacity of the SDS micelle-coated Fe 3 O 4 / SiO 2 MNPs was 16.37 mg g −1 for the removal of crystal violet.…”
Section: Adsorption Capacity and Isothermsmentioning
confidence: 95%
See 2 more Smart Citations
“…The TEM morphologies of Fe 3 O 4 @surfactants magnetic nanoparticles are shown in figure 3 . Figure 3 shows that the nano-Fe 3 O 4 cores indicated by dark colour are surrounded by a micellar shell of surfactants, along with the presence of slight agglomeration [ 45 ]. The TEM images of Fe 3 O 4 modified by SDS, CTAB and zwitterionic surfactant show the presence of spherical-like shapes having an average diameter of less than 20 nm.…”
Section: Resultsmentioning
confidence: 99%